Model Penerapan Teori Relevance dalam Analisis Drama - Adriansyah Abu Katili (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This article is intended to serve as a model for drama analysis using a pragmatik approach, applying the relevance theory proposed by Sperber and Wilson. The play used as an example is Arthur Miller's "Death of a Salesman." The author presents dialogue between the play's characters as material for analyzing meaning. This meaning lies at the level of explicature, high-level explicature, and implicature. It is hoped that students will be able to apply this analysis model in their final assignments.